Duration of diabetes as an important risk factor of microalbuminuria in type 2 diabetes - Indriani, Vitasari; Lestari, Tri; Dewantari, Vidya (Universa Medicina, 2020)
BACKGROUNDMicroalbuminuria is the earliest evidence of diabetic nephropathy and a major predictor of end stage renal disease (ESRD). The objective of the study was to determine the influence of several risk factors on the presence of microalbuminuria in type 2 diabetics.METHODSThis observational cross-sectional study was done on 73 patients with type 2 diabetes, who attended the Prolanis program in Primary Health Care from May to November 2018. Detailed medical histories including duration of diabetes and relevant clinical examinations including fasting blood sugar (FBS), post-prandial blood sugar (PPBS), HbA1c, serum creatinine, blood urea and urinary microalbumin were recorded for each patient. A multiple regression analysis was used to analyze the data. The analysis was assessed at 5% level of significance.RESULTSMean age of study population was 51.89 ± 6.78 years with female preponderance (51.1%). Mean FBS, PPBS, HbA1c, duration of diabetes, systolic blood pressure, microalbuminuria and serum creatinine was 182.51 ± 74.63 mg/dL, 186.25 ± 26.72 mg/dL, 8.8 ± 1.83%, 9.37 ± 5.96 years, 118.44 ± 4.13 mmHg, 30.32 ± 3.2 mg/day and 1.33 ± 0.64 mg/dL respectively. Duration of diabetes and HbA1c were positively correlated with microalbuminuria (â=0.052; Beta =0.367; p<0.001 and â=0.058; Beta=0.363; p<0.001) respectively.CONCLUSIONSDuration of diabetes was the most important risk factor of microalbuminuria in type 2 diabetes patients. Therefore microalbuminuria can predict diabetic nephropathy earlier, as a warning to prevent further worsening of diabetic complications.